Prevalence of human papillomavirus in men who have sex with men in the era of an effective vaccine; a call to act. Issue 8 (24th March 2014) - Sadlier, C; Rowley, D; Morley, D; Surah, S; O'Dea, S; Delamere, S; O'Leary, J; Smyth, P; Clarke, S; Sheils, O; Bergin, C
<x xml:space="preserve">Abstract</x> Objectives The incidence of human papillomavirus (HPV)‐associated anal cancer is increasing. Men who have sex with men (MSM), particularly those coinfected with HIV, are disproportionately affected. Documenting the molecular epidemiology of HPV infection is important in guiding policy makers in formulating universal and/or targeted vaccine guidelines. Methods A prospective cohort study was conducted. HIV‐positive and HIV‐negative MSM > 18 years old were invited to participate. Provider‐performed anal swabs were collected and anal HPV infection was detected using consensus primer solution phase polymerase chain reaction (PCR) followed by type‐specific PCR for high‐risk (HR)‐HPV types 16, 18 and 31. Between‐group differences were analysed using χ2 tests and Wilcoxon rank tests. Results One hundred and ninety‐four MSM [mean (standard deviation (SD)) age 36 (10) years; 51% HIV‐positive) were recruited. The median number of sexual contacts in the preceding 12 months was 4 (interquartile range 2‐10). HIV‐positive subjects had a mean (SD) CD4 count of 557 (217) cells/μL, and 84% were on highly active antiretroviral therapy (HAART). Thirty‐one samples were B‐globin negative and thus excluded from further analysis. A total of 113 subjects (69%) had detectable HPV DNA. Sixty‐eight subjects (42%) had an HR‐HPV type detected. HR HPV type 16 was detected in 44 samples (27%), HR‐HPV type 18 in 26 samples (16%) and HR‐HPV type 31 in 14 samples (23%). Twenty‐eight subjects (17%) had more than one type of HR‐HPV type detected. When HPV and HR‐HPV were stratified by age, those > 35 years had a higher prevalence (P = 0.001 and P = 0.028, respectively). HIV‐positive subjects were more likely than HIV‐negative subjects to have any detectable HPV (77% vs. 61%, respectively; P = 0.04), to have HR‐HPV type 18 or 31 (P = 0.05 and P = 0.006, respectively) and to be infected with more than one HR‐HPV type (31% vs. 3%, respectively; P < 0.001). Within the HIV‐positive group, the prevalence of HPV was higher in those not on HAART (P = 0.041), although it did not differ when stratified by CD4 count. Conclusions The identified prevalence of anal HPV infection was high. Emerging patterns of HPV‐related disease strengthen the call for universal vaccination of boys and girls with consideration of catch‐up and targeted vaccination of high‐risk groups such as MSM and those with HIV infection.